Microstructure and Mechanical Properties of a Partially Recrystallized Aluminium Alloy having Varying Cu/Mg Ratio - Md. Jasim Uddin; Hossain Rashed (University of Muhammadiyah Malang, 2021)
Heat treatable Al-Zn-Mg-Cu alloys are widely used in automobile industries, aerospace and military applications. This study investigates the effects of different amounts of copper and magnesium on microstructure and mechanical properties. The as-cast alloys prepared in a permanent mould showed a dendritic microstructure and the intermetallic phase surrounded by secondary phases. As-cast microstructure was refined substantially during hot rolling processes. The ultimate tensile strength and hardness values both in hot-rolled and aged conditions along longitudinal and transverse directions were found greater for the alloy containing 1.33 wt.% copper and 1.01 wt.% magnesium, whereas strain to fracture values for alloy 01 with 1.09 wt.% copper and 1.8 wt.% magnesium. The fracture surface of the tensile sample having relatively lower amount of copper content revealed dimple rupture behaviour, while higher 4.32 wt.% copper content indicated transgranular and cleavage fracture. A similar pattern was also observed along the transverse direction. Overall, copper appeared to be more effective in strengthening of the studied alloys.